A novel routing protocol considering the boundary effects for ad hoc networks - Qingwen Wang; Haitao Yu (International Journal of Distributed Sensor Networks, 2020)
To alleviate the broadcast storm problem in the route discovery process, this article proposes a novel routing protocol considering the boundary effects for ad hoc networks, named NRP. The novelty of NRP lies in the following: first, NRP defines a forwarding area criterion considering the effects of the node transmission area boundary to reduce the broken links due to the mobility of nodes; second, NRP adopts the idea of a piecewise function to estimate the node degree when the nodes are in the center, borderline, and corner areas, respectively, which considers the effects of both network boundaries and node communication boundaries without broadcasting Hello messages periodically; third, NRP applies the static game forwarding strategy to calculate the forwarding probability during the route discovery process. NRP reduces the redundant retransmissions and collision probability among neighboring nodes, thus improving the forwarding efficiency. The extensive simulation results by NS-2 simulator have shown that NRP performs better than AODV + FDG, AODV + Hello, ad hoc on-demand distance vector, ad hoc on-demand multipath distance vector, and energy-efficient ant-based routing in terms of packet delivery ratio, routing overhead, normalized medium access control load, throughput, and network lifetime.